Principles of Mining: Valuation, Organization and Administration - Hoover, Herbert, 1874-1964 (Salt Lake City, UT : Project Gutenberg, 2008)
"Principles of Mining: Valuation, Organization and Administration" by Herbert Hoover is a scientific publication written in the early 20th century. This work serves as a comprehensive resource focused on the principles of mining, particularly the valuation, organization, and administration of various mineral resources including copper, gold, lead, silver, tin, and zinc. It highlights both theoretical and practical elements crucial for understanding the complexities of mining enterprises. The opening of the book establishes its foundational nature through a preface that outlines its purpose and origin as a condensation of lecture series delivered at prestigious universities. Hoover emphasizes the challenge of valuing mines due to numerous speculative factors while asserting the importance of both management and geological evidence in assessing a mine's worth. The initial chapter engages the reader with the specifics of mine valuation, detailing methods for determining average metal content through sampling and assay plans, thereby laying the groundwork for an in-depth discussion of the various complexities involved in the mining industry. (This is an automatically generated summary.)
Release date is 2008-09-24
Produced by Robert J. Hall
Keywords: Mines and mineral resources; Mining engineering; Mineral industries -- Finance